Detection of Aspergillus Species fungi that cause fungal diseases in Cyprinus carpio in Nabea Al-Sin farm - ابراهيم, رشا; كاترين منصور,; بلسم جريكوس , (Latakia University Journal -Biological Sciences Series, 2025)
Fish in farms are exposed to many fungal diseases caused by different genera of fungi, the most important are species of the genus Aspergillus, which causes aspergillosis. The aim of this research is to identify Aspergillus species that cause diseases in common carp Cyprinus carpio. In order to determine the extent of the spread of the disease and evaluate the condition of the fish at Nabea Al-Sin farm, 137 fish samples were collected form the rearing ponds based on the clinical signs represented by the presence of ulcers all over the fish's body, which was one of the clear signs with lacerations in the caudal, dorsal and pectoral fins, and the presence of dark spots on the skin. some fish suffered from bulging eyes (unilateral or bilateral), and fish samples showed mild to severe infection. The fish were microbiologically (fungal) examined, and samples were taken form the affected skin, external wounds, fins, gills, and intestines using multiplication medium Peptone Water and culture medium Poteto Dextrose Agar (PDA). After incubation, the developing fungal species were isolated in order to purify and identify them. The results showed the presence of three species belonging to the genus Aspergillus, A.niger, A.flavus, A.fumigatus.